Anti-EGFR-resistant clones decay exponentially after progression: implications for anti-EGFR re-challenge. (21st November 2018) - Parseghian, C M; Loree, J M; Morris, V K; Liu, X; Clifton, K K; Napolitano, S; Henry, J T; Pereira, A A; Vilar, E; Johnson, B; Kee, B; Raghav, K; et al.
Abstract: Background: Colorectal cancer (CRC) has been shown to acquire RAS and EGFR ectodomain mutations as mechanisms of resistance to epidermal growth factor receptor (EGFR) inhibition (anti-EGFR). After anti-EGFR withdrawal, RAS and EGFR mutant clones lack a growth advantage relative to other clones and decay; however, the kinetics of decay remain unclear. We sought to determine the kinetics of acquired RAS/EGFR mutations after discontinuation of anti-EGFR therapy. Patients and methods: We present the post-progression circulating tumor DNA (ctDNA) profiles of 135 patients with RAS / BRAF wild-type metastatic CRC treated with anti-EGFR who acquired RAS and/or EGFR mutations during therapy. Our validation cohort consisted of an external dataset of 73 patients with a ctDNA profile suggestive of prior anti-EGFR exposure and serial sampling. A separate retrospective cohort of 80 patients was used to evaluate overall response rate and progression free survival during re-challenge therapies. Results: Our analysis showed that RAS and EGFR relative mutant allele frequency decays exponentially ( r 2 =0.93 for RAS ; r 2 =0.94 for EGFR ) with a cumulative half-life of 4.4 months. We validated our findings using an external dataset of 73 patients with a ctDNA profile suggestive of prior anti-EGFR exposure and serial sampling, confirming exponential decay with an estimated half-life of 4.3 months. A separate retrospective cohort of 80 patients showed that patients had a higher overall response rate during re-challenge therapies after increasing time intervals, as predicted by our model. Conclusion: These results provide scientific support for anti-EGFR re-challenge and guide the optimal timing of re-challenge initiation.